ASSESSMENT OF LYMPHOID NEOPLASM RISK FACTORS IN PEOPLE OCCUPATIONALLY EXPOSED TO PROLONGED IONIZING RADIATION - D. E. Kalinkin; A. B. Karpov; D. E. Maksimov; E. N. Kiriakidi; R. M. Takhauov (Сибирский онкологический журнал)
Objective: To estimate the incidence of malignant neoplasms of lymphoid tissue (MNLT) among employees of the siberian chemical combine (SCC) occupationally exposed to prolonged ionizing radiation.Material and methods. The study included 44,041 employees of the SCC, of whom 16,938 were occupationally exposed to prolonged low-intensity ionizing radiation (IR). Of 295 cases with hemoblastoses, there were 89 with occupational exposure to IR. The structure and incidence of hemoblastoses (based on the number of person-years of observation, (PYO), as well as the standardized relative risk (SRR) of their development and excess relative risk (err) per unit dose of radiation (GR) were evaluated. Calculation of SRR was carried out for the following intervals of the total dose of external exposure: 0; >0–0.05; >0.05–0.10; >0.10-0.15; >0.15–0.20; >0.20-0.30; >0.30-0.50; >0.5–1.0; ≥ 1.0 Gy. The control group consisted of occupationally non-exposed employees of the SCC. The calculation of SRR and err was performed using the poisson regression using the amfit module of the EPICURE package.Results. The incidence of MNLT among males of SCC was 17.1 per 100,000 PYO, with the highest incidence rates for Non-Hodgkin’s lymphoma (NHL), chronic lymphocytic leukemia (CLL) and chronic leukemia (CL) excluding CLL. Among females of the SCC, the incidence of MNLT was 21.3 per 100,000 PYO. It was found that in none of the intervals of the external exposure there was no statistically significant excess of the SRR compared with the control group. The results of ERR/GY calculation also did not demonstrate the increased risk of hemoblastosis among people occupationally exposed to IR.Conclusion. Occupational exposure in the studied dose range does not increase the risk of developing MNLT.